Preparation method of porous alkaline composite diaphragm regulated and controlled by double pore-foaming agents

Through the preparation method of porous alkaline composite diaphragm controlled by double porogen, the problems of high cost, high technical difficulty, low hydrogen purity and potential dangers of gas cross-safety in the prior art are solved, and the efficient and low-cost hydrogen production effect is achieved.

CN119710821APending Publication Date: 2025-03-28SHANGHAI ENERGY NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411876969.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic composite separators face the problems of high material cost, high technical difficulty, low hydrogen purity and potential safety of gases in the efficient hydrogen production process.

Method used

A porous alkaline composite separator is prepared by a double pore agent-regulated method. By combining materials such as polysulfone, N-methylpyrrolidone, polyethylene glycol, polyvinylpyrrolidone and nanoZrO2, a homogeneous slurry is formed and filled into the support polyphenylene sulfide fabric mesh. The composite separator has rich nano-scale pores and excellent hydrophilic properties.

Benefits of technology

The composite separator has achieved high electrolytic performance, high gas purity and high durability, meets industrial application requirements, and reduces material costs and technical difficulties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710821A_ABST
    Figure CN119710821A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a porous alkaline composite diaphragm regulated and controlled by double pore-foaming agents, which comprises the following steps: adding polysulfone into N-methyl pyrrolidone, stirring until the polysulfone is completely dissolved, then adding and dissolving pore-foaming agents polyethylene glycol and polyvinylpyrrolidone into a homogeneous solution; adding nano ZrO2 into the homogeneous solution, and stirring to obtain uniform slurry; and filling the uniform slurry into meshes of a support body polyphenylene sulfide fabric, respectively passing through an air bath and a coagulating bath, taking out, and naturally airing to obtain the porous alkaline composite diaphragm. The internal pore structure and the hydrophilic performance of the composite diaphragm are adjusted through the pore-foaming agent, and meanwhile good thermal / chemical stability, mechanical stability and water electrolysis performance of the composite diaphragm are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen production by alkaline water electrolysis, and in particular to a method for preparing a porous alkaline composite diaphragm regulated by a dual porogen. Background Art

[0002] Hydrogen is an ideal energy source with zero pollution, sustainability, abundant sources and high energy density in the 21st century. Many countries have promoted it to a national strategic energy source. At present, the demand for hydrogen at home and abroad is increasing year by year, so high-efficiency, low-cost and high-safety hydrogen production technology is the current development goal. Low-temperature alkaline water electrolysis technology is an ideal hydrogen production technology due to its high maturity, low cost and superior performance. However, the current alkaline water electrolysis technology still faces problems such as high material cost and high technical difficulty. Alkaline electrolyzers are mainly composed of electrodes, catalysts and diaphragms. Most of the electrodes are made of nickel-iron materials, and the catalysts are non-precious metal catalysts. These components are widely used in the energy field. As a key component that separates the anode and cathode in the alkaline water electrolysis device, the diaphragm has developed from the initial asbestos mesh and polyphenylene sulfide fabric to a porous composite diaphragm after several generations of technology iterations.

[0003] The ideal alkaline water electrolysis composite diaphragm has favorable hydroxide conductivity, excellent alkaline aqueous solution wettability and permeability to prevent gas crossover. Under the conventional operating conditions of alkaline water electrolysis (usually 30% KOH aqueous solution, temperature 80°C), high mechanical properties, thermal / chemical stability and electrolytic performance stability are required. The composite diaphragm model ZIRFON UTP 500 of the Belgian AGFA company has become a typical representative of the current porous composite diaphragm with low surface resistance, good hydrophilicity, high bubble point pressure and excellent electrolytic performance. However, its high price hinders the large-scale promotion and application of domestic technology. In order to ensure the good hydrogen production performance of the porous alkaline composite diaphragm, it is required to maintain good pore permeability inside the composite diaphragm. However, the high-density porosity will cause the bubble point pressure of the composite diaphragm to drop, thereby affecting the purity of hydrogen, and bringing potential safety hazards caused by gas crossover. In addition, due to the hydrophobic structure of the polysulfone (PSU) framework of the composite diaphragm itself, the energy consumption of water electrolysis is further increased. Therefore, selecting suitable porogens to adjust the internal pore structure of the composite membrane is crucial to the water electrolysis performance.

[0004] Usually, traditional porogens are mostly polyvinylpyrrolidone (PVP), which is widely used in the preparation of sewage filtration membranes because it can increase the permeability of the pores in the membrane. However, using PVP as a single component as a porogen, due to its limited hydrophilic / hydrophobic properties with inorganic nanofillers and polymer PSU, it is impossible to achieve smaller nanoscale pore structure regulation. For example, patent No. CN202410072649.8 proposes a method for preparing a polysulfone / inorganic composite diaphragm for alkaline water electrolysis, reporting that low molecular weight polysulfone and high molecular weight polysulfone are mixed to improve the strength of the membrane, but the hydrophilic properties are not improved; for another example, patent No. CN202211698396.2 proposes a method for preparing an organic-inorganic composite diaphragm for alkaline water electrolysis and hydrogen production, reporting that the electrolysis efficiency is improved by uniformly distributing inorganic particles on the surface and inside of the diaphragm, but the micron- and nano-scale pores are not uniformly regulated. Therefore, it is of great significance to develop alkaline water electrolysis composite diaphragms with high electrolysis performance, high gas purity, high durability, and the ability to meet the requirements of industrial applications. Summary of the invention

[0005] The present invention adjusts the internal pore structure and hydrophilicity of the composite diaphragm through a porogen, while maintaining good thermal / chemical stability, mechanical stability and water electrolysis performance of the composite diaphragm.

[0006] The present invention is implemented in this way:

[0007] A preparation method of a porous alkaline composite diaphragm regulated by a dual porogen comprises: adding polysulfone to N-methylpyrrolidone and stirring until completely dissolved, then adding porogens polyethylene glycol and polyvinylpyrrolidone and dissolving them into a homogeneous solution; adding nano ZrO2 to the homogeneous solution and stirring to obtain a uniform slurry; and filling the uniform slurry into the mesh of a supporting polyphenylene sulfide fabric, passing through an air bath and a coagulation bath respectively, taking out and drying naturally to obtain a porous alkaline composite diaphragm.

[0008] For example, the step of filling the uniform slurry into the mesh of the support polyphenylene sulfide fabric includes: pouring the uniform slurry onto a slit coater, passing the support polyphenylene sulfide fabric through the slit so that the uniform slurry is bidirectionally cast and uniformly filled into the mesh of the support polyphenylene sulfide fabric.

[0009] For example, the molecular weight of the polysulfone is 5,000 to 20,000, the molecular weight of the polyethylene glycol is 200 to 10,000, and the molecular weight of the polyvinyl pyrrolidone is 10,000 to 300,000.

[0010] For example, the particle size of the nano ZrO2 is 10 nm to 500 nm.

[0011] For example, the mass ratio of the polysulfone to the N-methylpyrrolidone is 1:(1 to 8).

[0012] For example, the mass ratio of the polyethylene glycol to the polyvinyl pyrrolidone is 1:(1 / 3 to 3).

[0013] For example, the mass ratio of the whole of the polyethylene glycol and the polyvinyl pyrrolidone to the polysulfone is 1:(1 to 5).

[0014] For example, the mass ratio of the nano ZrO2 to the polysulfone is 1:(1 to 8).

[0015] For example, the time of passing through the air bath is 10 min to 90 min.

[0016] For example, the coagulation bath is an ethanol bath, and the time for passing through the coagulation bath is 10 min to 90 min.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) Abundant nanoscale pores: The present invention uses highly alkali-resistant PSU and high mechanical strength PPS fabric as the matrix and support, respectively, and utilizes the compatibility and phase separation characteristics of PVP and PEG. By changing the doping ratio of the two porogens PVP and PEG, the internal conductive pore size of the composite membrane is synergistically regulated to form a rich staggered nanoscale pore structure, while improving the hydrophilicity of the composite membrane.

[0019] (2) Excellent hydrophilicity, high conductivity and high bubble point pressure: In the PVP and PEG dual porogen synergistic strategy of the present invention, PEG contains a large number of hydroxyl groups and has a highly hydrophilic property, which significantly improves the hydrophilicity of the composite membrane and absorbs more KOH. At the same time, it forms a supramolecular hydrogen bond network with nano ZrO2, which accelerates OH - The dual effects of conducting and increasing the number of carriers significantly improve the conductivity. On this basis, the bubble point pressure of the composite diaphragm can be effectively increased by adjusting the appropriate air bath time.

[0020] (3) Excellent water electrolysis performance: The PVP and PEG dual porogen synergistic regulation method of the present invention can form a more compact hydrophilic pore structure inside the composite membrane, exert excellent conduction efficiency, enhance ion transmission capacity and improve conductivity while reducing gas cross-permeation. When applied to alkaline water electrolysis to produce hydrogen, the composite membrane of the present invention can achieve a current density of up to 13000A / m at a cell voltage of 2V. 2 , meeting the conditions for commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1a and 1bThey are the SEM images of the porous composite membrane controlled by PVP30 / PEG10 dual porogens under different viewing angles;

[0022] Figure 2 To regulate the conductivity and bubble point pressure of different PVP30 / PEG10 mass ratios in porous composite membranes;

[0023] Figure 3 To regulate the conductivity and bubble point pressure of porous composite membranes with different air bath times;

[0024] Figure 4 In order to apply the porous composite membrane to the actual single electrolyzer, the polarization curves at 30% KOH solution and 80°C operating temperature were obtained;

[0025] Figure 5 This is the contact angle measurement diagram of the porous composite membrane. DETAILED DESCRIPTION

[0026] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] The embodiment of the present invention provides a method for preparing a porous alkaline composite membrane regulated by a dual porogen, and the prepared membrane can be applied to alkaline water electrolyzers and related energy devices. The detailed process of the preparation method is described below:

[0029] First, polysulfone is added to N-methyl pyrrolidone and stirred until completely dissolved, and then porogen polyethylene glycol and polyvinyl pyrrolidone are added and dissolved into a homogeneous solution. The time for adding polysulfone to N-methyl pyrrolidone and stirring can be, but is not limited to, 12 hr to 36 hr, preferably 12 hr, 13 hr, 14 hr, 15 hr, 16 hr, 17 hr, 18 hr, 19 hr, 20 hr, 21 hr, 22 hr, 23 hr, 24 hr, 25 hr, 26 hr, 27 hr, 28 hr, 29 hr, 30 hr, 31 hr, 32 hr, 33 hr, 34 hr, 35 hr, or 36 hr.

[0030] The molecular weight of the polysulfone may be, but is not limited to, 5,000 to 20,000, preferably 5,000, 6,000, 7,000, 8,000, 9,000, 10,000, 11,000, 12,000, 13,000, 14,000, 15,000, 16,000, 17,000, 18,000, 19,000, or 20,000. The molecular weight of polyethylene glycol can be, but is not limited to, 200 to 10,000, preferably 200, 400, 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400, 2600, 2800, 3000, 3200, 3400, 3600, 3800, 4000, 4200, 4400, 4600. , 4800, 5000, 5200, 5400, 5600, 5800, 6000, 6200, 6400, 6600, 6800, 7000, 7200, 7400, 7600, 7800, 8000, 8200, 8400, 8600, 8800, 9000, 9200, 9400, 9600, 9800, or 10000. The molecular weight of polyvinyl pyrrolidone may be, but is not limited to, 10,000 to 300,000, preferably 10,000, 20,000, 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 200,000, 210,000, 220,000, 230,000, 240,000, 250,000, 260,000, 270,000, 280,000, 290,000, or 300,000.

[0031] The mass ratio of polysulfone to N-methylpyrrolidone may be, but is not limited to, 1:(1 to 8), preferably 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or 1:8. The mass ratio of polyethylene glycol to polyvinyl pyrrolidone may be, but is not limited to, 1:(1 / 3 to 3), preferably 1:1 / 3, 1:2 / 3, 1:1, 1:2, or 1:3. The ratio between the total mass of polyethylene glycol and polyvinyl pyrrolidone and the mass of polysulfone may be, but is not limited to, 1:(1 to 5), preferably 1:1, 1:2, 1:3, 1:4, or 1:5.

[0032] Then, with nano ZrO add in the homogeneous phase solution, stir and obtain uniform slurry.Nano ZrO particle diameter can be but not limited to 10nm to 500nm, preferably 10nm, 50nm, 100nm, 200nm, 300nm, 400nm or 500nm.Chilling time can be but not limited to 12hr to 36hr, preferably 12hr, 13hr, 14hr, 15hr, 16hr, 17hr, 18hr, 19hr, 20hr, 21hr, 22hr, 23hr, 24hr, 25hr, 26hr, 27hr, 28hr, 29hr, 30hr, 31hr, 32hr, 33hr, 34hr, 35hr or 36hr. The mass ratio of nano ZrO2 to polysulfone can be, but is not limited to, 1:(1 to 8), preferably 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, or 1:8.

[0033] Finally, the uniform slurry is filled into the mesh of the support polyphenylene sulfide fabric, and passed through an air bath and a coagulation bath respectively, and then taken out and dried naturally to obtain a porous alkaline composite diaphragm. When the uniform slurry is filled into the mesh of the support polyphenylene sulfide fabric, it can be, but not limited to, pouring the uniform slurry into a slit coater, passing the support polyphenylene sulfide fabric through the slit so that the uniform slurry is bidirectionally cast and uniformly filled into the mesh of the support polyphenylene sulfide fabric. The time of passing through the air bath can be, but not limited to, 10 min to 90 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, or 90 min. The coagulation bath can be, but not limited to, an ethanol bath, and the time of passing through the coagulation bath can be, but not limited to, 10 min to 90 min, preferably 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, or 90 min.

[0034] The following examples illustrate the present invention, wherein the PSU used has a molecular weight of 8000, the PEG is PEG10, has a molecular weight of 1000, and the PVP is PVP30, has a molecular weight of 30000:

[0035] Example 1

[0036] This embodiment provides a method for preparing a porous alkaline composite membrane regulated by a dual porogen, and the steps are as follows:

[0037] Step 1: Dissolve PSU in NMP, control the mass ratio of PSU to NMP to be 1:4, and mechanically stir until completely dissolved to obtain a PSU solution. Add two porogens, PVP30 and PEG10, with a mass ratio of 1.5:0.5, to the PSU solution and stir thoroughly until a clear solution is obtained to obtain a homogeneous solution, and control the mass ratio of the porogen to PSU to be 2:5.

[0038] Step 2: Add nano ZrO2 with a particle size of 100 nm to the homogeneous solution obtained in step 1, wherein the mass ratio of nano ZrO2 to PSU is 1:4, and stir thoroughly to obtain a milky white slurry.

[0039] Step 3: Pour the slurry obtained in step 2 onto a slit coater, and the slurry is evenly cast in the mesh of the PPS fabric supporting body through the slit. After being in an air bath for 30 minutes, it is placed in an ethanol bath for 30 minutes, taken out and naturally dried to obtain the porous alkaline composite diaphragm of this embodiment.

[0040] The surface and cross-sectional micromorphology of the composite membrane prepared in Example 1 were characterized by scanning electron microscopy (SEM). Figure 1a and 1b As shown in Figure 2, PVP30 / PEG10 has a good pore-forming effect on the polymer. Figure 1a In the membrane, the pores are abundant and uniform, and the polysulfone framework is intact. Figure 1b In the figure, further pore magnification revealed that the pores were composed of 500nm to 1um staggered microporous structures, and ZrO2 was evenly dispersed inside the composite membrane. The above showed that under the synergistic effect of the two porogens, a rich staggered nano-microporous structure could be formed, which could not only effectively improve the OH - transmission capacity while effectively reducing gas cross-permeation.

[0041] Example 2

[0042] According to the preparation process of the porous alkaline composite membrane regulated by the dual porogens in Example 1, this example prepares the porous alkaline composite membrane by adjusting the mass ratio of the two porogens PEG10 / PVP30, and the steps are as follows:

[0043] Step 1: Dissolve PSU in NMP, control the mass ratio of PSU to NMP to be 1:4, and mechanically stir for 24 hours until it is completely dissolved to obtain a PSU solution. Then, two porogens with mass ratios of PVP30 and PEG10 of 2:0, 1.5:0.5, 1:1, 0.5:1.5, and 0:2 are added to the PSU solution and fully dissolved to obtain a homogeneous solution, and the mass ratio of the porogen to PSU is controlled to be 2:5.

[0044] Step 2: Add nano ZrO2 with a particle size of 100 nm to the homogeneous solution obtained in step 1, wherein the mass ratio of nano ZrO2 to PSU is 1:4, and stir thoroughly to obtain a milky white slurry.

[0045] Step 3: Pour the slurry obtained in step 2 onto a slit coater, and allow the slurry to be bidirectionally cast through the slit and evenly filled into the mesh of the support PPS fabric. After being in an air bath for 30 minutes, place it in an ethanol bath for 30 minutes, take it out and dry it naturally to obtain the porous alkaline composite diaphragm of this embodiment.

[0046] The porous composite membrane was cut into discs with a radius of 0.5 cm, loaded into the PTFE electrode test device, and externally connected to the Chenhua electrochemical workstation CH-760E. The scanning frequency range was set to 0.1 Hz to 1000000 Hz, and the voltage amplitude was set to 0.1 V (room temperature). The ionic conductivity of the composite membrane was measured by AC impedance method. At the same time, referring to GB / T 26204-2010 "Performance test method of liquid phase filter materials: air bubble point test", the porous composite membrane was cut into discs with a radius of 0.5 cm to measure the bubble point pressure and maximum pore size.

[0047] like Figure 2 As shown in the figure, the mixture of PEG10 and PVP30 can significantly improve the conductivity and bubble point pressure, especially the mixture of PEG10 and PVP30 in the ratio of 1.5:0.5 reaches the highest conductivity and bubble point pressure. Figure 2 The conductivity and bubble point pressure obtained by mixing in the ratio shown are greater than those of PEG10 and PVP30 alone. This shows that the excellent hydrophilicity of PEG10 can form a strong hydrogen bond network with nano ZrO2, which can effectively improve the conductivity. At the same time, the suitable compatibility and phase separation characteristics of PEG10 and PVP30 can be used as dual porogens to synergistically adjust the pore structure, pore density and pore size. In addition, the addition of PEG10 optimizes the microscopic component structure of the membrane and increases the bubble point pressure of the membrane, thereby effectively preventing gas crossover.

[0048] Example 3

[0049] According to the preparation process of the porous alkaline composite membrane regulated by the dual porogen in Example 1, this example prepares the porous alkaline composite membrane by regulating the time of different air baths, and the steps are as follows:

[0050] Step 1: PSU was dissolved in NMP, the mass ratio of PSU to NMP was controlled to be 1:4, and mechanical stirring was performed until it was completely dissolved to obtain a PSU solution. Subsequently, two porogens, PVP30 and PEG10, were added to the PSU solution at a mass ratio of 1.5:0.5, and stirred thoroughly until a clear solution was obtained to obtain a homogeneous solution, and the mass ratio of the porogen to PSU was controlled to be 2:5.

[0051] Step 2: Add nano ZrO2 with a particle size of 100 nm to the homogeneous solution obtained in step 1, wherein the mass ratio of nano ZrO2 to PSU is 1:4, and stir thoroughly for 24 hours to obtain a milky white slurry.

[0052] Step 3: Pour the slurry obtained in step 2 onto a slit coater, and the slurry is evenly cast in the mesh of the PPS fabric supporting body through the slit, and then air bathed for 10 minutes, 30 minutes, 50 minutes, 70 minutes, and 90 minutes, respectively. Then, it is placed in an ethanol bath for 30 minutes, taken out and naturally dried to obtain the porous alkaline composite diaphragm of this embodiment.

[0053] The porous composite membrane was cut into discs with a radius of 0.5 cm, and the conductivity and bubble point pressure of the composite membrane were measured in the same manner as in Example 2. Figure 3 As shown in the figure, as the air bath time increases, the bubble point pressure of the membrane increases significantly. After 90 minutes of air bath, the composite membrane has the best comprehensive performance of 3.86 bar high bubble point pressure and 0.65 S / cm high conductivity.

[0054] Example 4

[0055] According to the preparation process of the porous alkaline composite diaphragm regulated by the dual porogen in Example 1, this example provides a small-scale electrolytic cell alkaline water electrolysis experiment. The composite diaphragm was cut into 2cm×2cm square pieces and immersed in a 30% KOH solution for activation for 24h. After being taken out, it was loaded into the electrolytic cell, and Raney nickel was used as an electrode. The electrolyte was heated to control the electrolyte temperature to be maintained at 80°C, wherein the electrolyte was a 30% KOH aqueous solution, and the electrolyte flow rate was controlled by a peristaltic pump to be 200r / min.

[0056] The polarization curve is Figure 4 As shown in the figure, by controlling the current size, the current measurement range is 0.05A to 2A, and the voltage size of the electrolytic cell is recorded. It can be seen from the figure that under a cell voltage of 2V, the current density of the composite diaphragm of the present invention can be as high as 13000A / m 2 , meeting the conditions for commercial application.

[0057] Example 5

[0058] According to the preparation process of the porous alkaline composite membrane in Example 1, this example provides a water contact angle experiment. The composite membrane is cut into 1 cm × 4 cm square pieces and placed in an oven at 50°C for 5 hours to remove residual moisture in the membrane. Then, the flat composite membrane is placed on a smooth glass sheet, and the water contact angle of the obtained porous composite membrane is measured with reference to GB / T 30693-2014 "Measurement of the contact angle of plastic film with water".

[0059] The results are as follows Figure 5 As shown, the water contact angle measured at the moment when the water droplet contacts the composite membrane is about 48 degrees. The composite membrane has good water affinity, indicating that the composite membrane not only has a uniform and stable pore structure under the regulation of the dual porogen, but also exhibits good hydrophilic properties, which is beneficial to the conduction of hydroxide ions.

[0060] The above contents involving common knowledge are not described in detail, and those skilled in the art can understand them.

[0061] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a porous alkaline composite membrane regulated by a dual porogen, characterized in that: include: Add polysulfone to N-methylpyrrolidone and stir until completely dissolved, then add porogens polyethylene glycol and polyvinylpyrrolidone and dissolve into a homogeneous solution; Adding nano ZrO2 into the homogeneous solution and stirring to obtain a uniform slurry; as well as The uniform slurry is filled into the mesh of the supporting polyphenylene sulfide fabric, passed through an air bath and a coagulation bath respectively, taken out and naturally dried to obtain a porous alkaline composite diaphragm.

2. The method for preparing a porous alkaline composite membrane regulated by a dual porogen according to claim 1, characterized in that: The step of filling the uniform slurry into the mesh of the support polyphenylene sulfide fabric includes: pouring the uniform slurry onto a slit coater, passing the support polyphenylene sulfide fabric through the slit so that the uniform slurry is bidirectionally cast and uniformly filled into the mesh of the support polyphenylene sulfide fabric.

3. The method for preparing a porous alkaline composite membrane regulated by a dual porogen according to claim 1, characterized in that: The molecular weight of the polysulfone is 5000 to 20000, the molecular weight of the polyethylene glycol is 200 to 10000, and the molecular weight of the polyvinyl pyrrolidone is 10000 to 300000.

4. The method for preparing a porous alkaline composite membrane regulated by a dual porogen according to claim 1, characterized in that: The particle size of the nano ZrO2 is 10nm to 500nm.

5. The method for preparing a porous alkaline composite membrane controlled by a dual porogen according to claim 1, characterized in that: The mass ratio of the polysulfone to the N-methylpyrrolidone is 1:(1 to 8).

6. The method for preparing a porous alkaline composite membrane regulated by a dual porogen according to claim 1, characterized in that: The mass ratio of the polyethylene glycol to the polyvinyl pyrrolidone is 1:(1 / 3 to 3).

7. The method for preparing a porous alkaline composite membrane controlled by a dual porogen according to claim 6, characterized in that: The mass ratio of the polyethylene glycol and the polyvinyl pyrrolidone as a whole to the polysulfone is 1:(1 to 5).

8. The method for preparing a porous alkaline composite membrane controlled by a dual porogen according to claim 1, characterized in that: The mass ratio of the nano ZrO2 to the polysulfone is 1:(1 to 8).

9. The method for preparing a porous alkaline composite membrane controlled by a dual porogen according to claim 1, characterized in that: The time of passing through the air bath is 10 min to 90 min.

10. The method for preparing a porous alkaline composite membrane controlled by a dual porogen according to claim 1, characterized in that: The coagulation bath is an ethanol bath, and the time of passing through the coagulation bath is 10 minutes to 90 minutes.

Citation Information

Patent Citations

  • Organic-inorganic composite diaphragm for hydrogen production from alkaline electrolyzed water and preparation method of organic-inorganic composite diaphragm

    CN115928145A

  • Preparation method of polysulfone / inorganic composite diaphragm for alkaline electrolyzed water

    CN117702183A